Erratum: "Visualization of soft tissues by highly sensitive X-ray crystal analyzer-based multi diffraction enhanced imaging". (30th August 2016) - Wu, Yanlin; Sunaguchi, Naoki; Lin, Xiaojie; Wang, Yongting; Yuasa, Tetsuya; Hirano, Keiichi; Hyodo, Kazuyuki
Abstract :